Crowdfunding in the Spanish Publishing Industry - Magadán Díaz, Marta; Rivas García, Jesús Israel (Publishing Research Quarterly, 2019)
This article analyzes the effects of crowdfunding on the processes of generating value in Spanish publishing companies in order to understand the extent to which their use can be integrated and modify the existing publishing business models. Through a qualitative approach (case study), the type of publishing company that uses this formula will be determined, the nature of the publishing projects where it is applied and the type of crowdfunding that is most frequently used, to conclude that crowdfunding is used in Spain: (a) by small publishing companies, (b) in those publishing projects that exceed the capacity of a publishing organization to obtain the necessary resources through traditional channels, and (c) in its modality of non-monetary rewards.
Keywords: crowdfunding; publishing industry; value chain; business model; case method; JCR; Scopus